Microwave-Assisted Synthesis and Fluorescent Properties of 4-Phenyl-1,8-naphthalimide - Frank Betancourt; James Helmkay; Hongbin Yan (Molbank, 2020)
4-Phenyl-1,8-naphthalimide was synthesized by imidation of commercially available 4-bromo-1,8-naphthalic anhydride, followed by Suzuki coupling with phenyl boronic acid, both under microwave heating. The microwave-assisted reactions were found to be faster and more efficient than reactions carried out by heating in oil-baths. While this compound was quite fluorescent in solvents such as chloroform, methanol and ethanol, it is virtually non-fluorescent in DMSO; however, upon the addition of water to DMSO solutions of this dye, fluorescence was restored, suggesting a tendency for aggregation-induced emission. The fluorescent properties of 4-phenyl-1,8-naphthalimide were found to be influenced by salt concentrations, likely as a result of hydrophobic effects. While this dye does not show binding to DNA, presence of bovine serum albumin leads to effective fluorescence quenching.